Anthropocene in a Media Perspective - Tække, Jesper (Journal of Sociocybernetics, 2025)
In this short, I introduce the article “From Media Evolution to the Anthropocene: Unpacking Sociotechnical Autopoiesis” and explore the concept of the Anthropocene from a media-theoretical perspective. The Anthropocene is commonly understood as the epoch in which human activity has become the dominant force shaping the planet’s climate, ecosystems, and geology. However, this concept is fraught with controversies concerning its dating, naming, causation, and appropriate responses.